Captar o passado: a película como estratégia de referencialidade histórica em “Era Uma Vez em… Hollywood” - Sales, Thalita Fernandes de (2022)
The present work seeks to investigate the use of analog films in the motion picture Once Upon a Time...in Hollywood. This investigation was based on film analysis to study how the past is evoked in the movie texture by analog film and cinematography choices. In order to do so, the research analyzed how 35mm, 16mm, and Super 8 film gauges refer to audiovisual production practices from the 60s, as well as visual codes and standards established by media culture. Furthermore, it aimed to study how the choice of analog film, in a means hegemonically digital, might be perceived as an author signature of director Quentin Tarantino. Lastly, it concludes that the use of different analog films and aspect ratios value the narrative, mention different audiovisual pieces produced between the 50s and 60s, and work together with production design, costume, and soundtrack to evoke the atmosphere of Los Angeles in 1969.